PARENTS’ IMPACT ON STUDENTS’ READING ACHIEVEMENT - Geske, Andrejs; Ozola, Antra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Scientific studies have proved that a family has a high impact on the students’ academic achievement, including their reading literacy. This paper focuses on the parents’ undertaken activities for promoting the development of child’s reading literacy at the preschool age (reading together, singing, discussing the read text with a child, playing together, etc.) to explore the impact of these activities upon the reading literacy achievement of students in Grade 4. The research problem addresses the following questions: whether and to what extent the parents’ undertaken activities for promoting the development of child’s reading literacy at the preschool age have an impact on students’ reading skills at the end of their fourth school year.The analysis is based on the research results from students’ tests, students’ and parents’ questionnaires of the Progress in International Reading Literacy Study (PIRLS) 2016, organised by the International Association for Evaluation of Educational Achievement (IEA). The impact of parents’ activities carried out together with their preschool aged children was studied performing a linear regression analysis along with a frequency and correlation analysis.A higher reading achievement was demonstrated by those fourth graders whose parents were actively involved in reading promotion activities. Although one determining activity could not be stated, reading together and storytelling were found to be significant. Parents’ education correlated positively with the frequency of their undertaken reading promotion activities; thus, the parents’ education was approved to have a multifaceted impact on a child’s reading achievement.